Model Tafsir Ayat-Ayat Ekologis Menurut Ulama Tafsir Kontemporer di Era Digital - Diman, Hasbullah (CV. Green Publisher Indonesia, 2025)
Global environmental degradation demands a reinterpretation of Qur’anic verses related to ecology. In this context, contemporary exegetes seek to develop models of interpretation that are relevant to ecological issues while utilizing digital advancements. This study aims to analyze the models of ecological Qur’anic interpretation proposed by contemporary scholars and to examine the influence of digitalization on their methods and dissemination. This research employs a qualitative approach using library research, focusing on the works of exegetes such as M. Quraish Shihab, Wahbah al-Zuhaili, and Hamka, as well as digital tafsir platforms. The analysis applies an ecotheological hermeneutic approach to identify patterns of ecological interpretation within contemporary tafsir. The findings reveal that contemporary exegetes formulate integrative ecological interpretation models that combine theological, ethical, and scientific dimensions as an expression of humanity’s responsibility as khalifah (stewards) to maintain environmental balance. The digital era provides broader opportunities for disseminating ecological tafsir through interactive media, fostering ecological awareness grounded in Islamic values. In conclusion, contemporary ecological tafsir highlights the synergy between revelation, science, and technology in addressing environmental crises. Digitalization plays a strategic role in enhancing Muslim society’s ecotheological literacy. Future research is recommended to explore the interactive and algorithmic dimensions of digital tafsir as a medium for environmental education based on Qur’anic principles.